2001
DOI: 10.1590/s0066-782x2001000300003
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in a female nursing staff-pattern of occurrence, diagnosis, and treatment

Abstract: The results point to the need to introduce hypertension control measures in this occupational group, because of the magnitude of the disease and the potential impact on diffusion of knowledge and measures to control hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
(26 reference statements)
1
18
1
2
Order By: Relevance
“…[23,24] In this study, the lack of association between SAH and psychosocial stress may be related to interference resulting from the employment stability given to workers of public institution, could have a minimized perception of the demands arising from the work process. This aspect has also been reported in other studies involving Brazilian and foreign public institutions.…”
Section: Discussionmentioning
confidence: 96%
“…[23,24] In this study, the lack of association between SAH and psychosocial stress may be related to interference resulting from the employment stability given to workers of public institution, could have a minimized perception of the demands arising from the work process. This aspect has also been reported in other studies involving Brazilian and foreign public institutions.…”
Section: Discussionmentioning
confidence: 96%
“…7) evaluated the health status of healthcare workers who received health checkups for fasting plasma glucose, cholesterol levels, triglyceride levels, and blood pressure, and found that metabolic derangements are the most important health problems for healthcare workers. Other studies have also reported a high prevalence of hypertension in hospital employees 8,9) . However, only a small number of studies have compared cardiovascular risk factors between various groups of healthcare workers who might experience different work-related hazards on their jobs.…”
mentioning
confidence: 89%
“…[15] A few reports exist on the prevalence of HTN among hospital employees outside Nigeria. For instance, some Brazilian studies reported prevalence rates of 26% [17] and 36% [18] among physicians and female nurses respectively.…”
Section: Introductionmentioning
confidence: 99%